PENGARUH PENGGUNAAN CEROBONG PEMANAS FUEL SPRAY TERHADAP ATOMISASI MINYAK JELANTAH SEBAGAI BAHAN BAKAR DENGAN ATOMIZER BERBASIS AIR-ASSIST - Kenan Ho, Christopher; Ghurri, Ainul; Parwata, I Made (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract Atomization is a disintegration process of liquid into droplet. In combustion atomization is needed to increase the efficiency. Waste cooking oil can be used as fuel in combustion with fuel spray method. However, waste cooking oil have contaminants and high viscosity which make it harder to atomize and combust. Air-assisted atomizer utilise pressurized air to produce sprays with liquid supplied at low flow rate. A heating funnel is used as a preheating treatment to improves the atomization by heating up the fuel spray off the atomizer. In this research, the experiment is conducted with and without heating funnel with waste cooking oil as fuel. The result shows the effects of heating funnel to fuel atomization. The usage of heating funnel increased the atomization percentage by 11.7% from 71.2% without heating funnel to 82.9% with heating funnel. Keywords: Atomization, Droplet, Fuel Spray, Atomizer, Air-Assisted Atomizer, Heating Funnel, Preheating